2020
DOI: 10.21203/rs.3.rs-28577/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mitochondrial K-ATP channel opener diazoxide upregulates STIM1 and Orai1 via ROS and the MAPK pathway in adult rat cardiomyocytes

Abstract: Background: Openers of mitochondrial adenosine triphosphate-dependent potassium (mKATP) channels like diazoxide increase reactive oxygen species (ROS) production in cardiac cells and reduce Ca2+ elevations produced by ischemia-reperfusion, protecting the heart from damage. In this study we tested the hypothesis that opening mKATP channels regulates expression of the major components of store-operated Ca2+ entry (SOCE) STIM1 and Orai1.Results: Quantitative reverse transcriptase polymerase chain reaction (qRT-PC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…These results are consistent with those of in vitro experiments. A recent study of cardiomyocytes reported that KATP channel opening activated the p‐ERK pathway [38]. Therefore, we hypothesize that levosimendan might improve AKI after CPR in rats by activating the ERK pathway.…”
Section: Discussionmentioning
confidence: 87%
“…These results are consistent with those of in vitro experiments. A recent study of cardiomyocytes reported that KATP channel opening activated the p‐ERK pathway [38]. Therefore, we hypothesize that levosimendan might improve AKI after CPR in rats by activating the ERK pathway.…”
Section: Discussionmentioning
confidence: 87%